Exercise intervention in treatment-resistant major depressive disorder : benefits of accelerometer monitoring - Mota-Pereira, Jorge (2013)
Although there are several reports on the benefits of exercise on Major Depressive Disorder, none has monitored these exercise programs with accelerometers. We have conducted a 12 week home based moderate intensity exercise program in 33 treatmentresistant Major Depressive Disorder patients and, based on accelerometer data, determined compliance, exercise patterns and relationship between time spent in MVPA, response to treatment and Quality of Life. Patients were diagnosed according to DSM-IV criteria, and, from 150 initially screened, 33 met study criteria and were included. Four patients were excluded due to non-compliance/drop-out, thus a total of 29 patients finished the study. Patients were randomized either to a moderate intensity exercise program, which consisted of 30-45 min/day walks, 5 days/week, for 12 weeks, plus usual pharmacotherapy (N=22) or regular daily activities plus usual pharmacotherapy (N=11). All participants wore an ActiGraph® GT1M accelerometer during the 12 weeks. Moderate to very vigorous physical activity (MVPA), HAMD17, BDI, GAF, CGI-S, WHOQOL-Bref and SF-36 were assessed. Results show a trend for increasing time spent in MVPA from no response to response and remission (p = 0.028), and medium to strong correlations between time spent in MVPA and better depression and functioning parameters. There was also a trend for increasing time spent in MVPA and improvement of some QoL domains, namely WHOQOL-Bref Physical domain and SF-36 Physical Functioning and General Health Domains (p < 0.05). Participants showed preference for exercising on weekdays and on specific periods of the day (p < 0.05). Therefore, we suggest that future implementation of effective exercise augmentation therapy programs in MDD patients should consider objective measures that allow the quantification of exercise and assessment of exercise patterns.